学霸 Academic Hero: An Investigation of an Informal Bilingual Volunteer Peer Teaching Model in Supporting Chinese International Students’ Learning - Xu, Jinqi; Keevers, Lynne (Journal of International Students, 2022)
The growth in the number of Chinese students in Western universities has prompted academics to explore different pedagogical practices suitable for diverse classrooms. Some persisting contradictions between Western and Eastern conceptions of education exist in the practices and institutional structures that students encounter daily. Designing appropriate curricular and learning activities is crucial to the embedding of Chinese international students’ learning experience in the West. Adopting a practice-based approach, this ethnographic study investigates how an informal bilingual volunteer peer teaching model, entailing a mix of pedagogical practices, contributed to improving Chinese international students learning experience in a Western context. This paper advocates a movement beyond the boundaries and the limits of the fixed pedagogies and turns toward diverse pedagogical practices in teaching Chinese students. This paper also provides new insights about curricular design for academic and institutional practices in order to further develop Chinese students’ positive learning experiences in the West.